2018
DOI: 10.5194/isprs-archives-xlii-4-w8-155-2018
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Land Cover Classification of Salt Marshes Using Uas Time-Series Imagery and an Open Source Workflow

Abstract: Salt marsh ecology classification is difficult using traditional coarse resolution remote sensing techniques. Salt marshes exhibit a spatial pattern of vegetation zonation that are visually identifiable using imagery that has an improved 0.04 meter per pixel resolution. This project applies high resolution unmanned aerial system (UAS) imagery to aid in multi-temporal classification of our study area (Horseneck Beach) in Westport, Massachusetts, USA. We flew a DJI Phantom Pro 3 at low-and high-tide to capture e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The methodology needs multiple improvements to enhance vegetation characterization and classification, including: (1) Accounting for environmental conditions, such as water level and soil moisture, which are dominant issues in tidal systems that may affect the reflectance in the near-infrared and consequently affect the assessment of the vegetation state (NDVI); and (2) automatic classification or semi-automatic classification, calibration of the UAV images, which will be essential to avoid misclassification and reduce lens distortion, as indicated by Myers et al (2018) [66]. Therefore, further research is needed to define algorithms and rules for the UAVs images classification.…”
Section: Methodological Limitations and Future Advancesmentioning
confidence: 99%
“…The methodology needs multiple improvements to enhance vegetation characterization and classification, including: (1) Accounting for environmental conditions, such as water level and soil moisture, which are dominant issues in tidal systems that may affect the reflectance in the near-infrared and consequently affect the assessment of the vegetation state (NDVI); and (2) automatic classification or semi-automatic classification, calibration of the UAV images, which will be essential to avoid misclassification and reduce lens distortion, as indicated by Myers et al (2018) [66]. Therefore, further research is needed to define algorithms and rules for the UAVs images classification.…”
Section: Methodological Limitations and Future Advancesmentioning
confidence: 99%
“…Whether commercial or FOSS, SfM-MVS software offer an opportunity for the conservation community to engage in new and novel remote sensing techniques. They can be utilised to create highly detailed maps and 2.5/3D data at local scales, now include FOSS options that are being successfully deployed for scientific research (3,4,5358,62,105) and can be incorporated into the existing FOSS remote sensing pipeline. With applications for Android smartphones such as the UAV Toolkit (67) or small, lightweight action cameras now available, combined with balloons, kites, drones, or even collecting data on the ground, there is an opportunity within the conservation sphere to start enabling remote sensing even at a grass-roots or community level, or in any situation where funding may be limited but this type of data desired.…”
Section: Resultsmentioning
confidence: 99%
“…MicMac is the more mature software of the two and was initially developed in 2003 by the French National Geographic Institute and French national school for geographic sciences (52) whereas ODM began as a concept presentation at the 2014 FOSS4G (Free and Open Source Software for Geospatial) conference in Seoul. Both have drawn attention from the scientific community, but with ODM being the newer option, the focus has primarily been on its development and initial quality testing (3,4,53,54). MicMac’s maturity has allowed for a deeper scrutiny (55,56), has been utilised as the primary SfM-MVS option in geomorphological studies (57) and has been shown to be comparable to both Pix4D and Agisoft Photoscan (Metashape) within a low sward grassland study (58).…”
Section: Open Source Sfm-mvsmentioning
confidence: 99%
See 1 more Smart Citation